Public Health Protection and Social Insurance: Reforming Legal Norms through Contextualized Islamic Economic Law - Ade fisti pongoliu; Abdul Razak; Marwati Riza; Sri Susyanti Nur; Uzodinma Yurriens (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Public health protection and social insurance represent foundational pillars in achieving equitable welfare across societies. In many Muslim-majority countries, however, existing social policies often fail to fully reflect Islamic legal values in a contextualized manner. This study aims to reformulate positive legal norms concerning public health and social protection through the lens of Islamic economic law. Employing a normative juridical approach, the study applies maqāṣid al-sharī‘ah as its primary theoretical framework, supported by literature reviews and comparative analysis of social policy models in selected Muslim-majority states. The findings reveal that integrating Islamic financial instruments—such as zakat for funding basic healthcare, productive waqf for health facility development, and social insurance schemes based on tabarru’ and ta’āwun can be practically implemented as viable alternatives to conventional systems. In Indonesia, policies grounded in these principles show strong potential to reduce the burden on the state budget (APBN) while simultaneously enhancing social solidarity. A contextualized application of Islamic economic law proves not only normatively sound but also practically effective in designing a socially just and resilient protection system capable of responding to contemporary challenges